Multiferroic based on nematic liquid crystal and nanoparticles - Kovalchuk, O.V.; Kovalchuk, T.M.; Kucheriavchenkova, N.M.; Sydorchuk, V.V.; Khalameida, S.V. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2016)
Multiferroics stable in morphological parameters has been created by introducing ferromagnetic (Fe₂O₃) and ferroelectric (LiNbO₃) nanoparticles with the concentration 0.3 wt.% into nematic liquid crystal 6СНВТ. Being based on the analysis of photos obtained in nonpolarized light of optical microscope, it has been shown that the average sizes of irregular geometric shape of aggregates of Fe₂O₃ nanoparticles range unities of micrometers and are one order higher than spherical aggregates of LiNbO₃ nanoparticles. It has been shown that low-frequency dispersion of components for the complex permittivity is caused by near-electrode processes. The mechanism of this relaxation process has been ascertained, and its parameters for some of the samples have been determined. It has been shown that when introducing the nanoparticles the conductance of liquid crystal decreases, which may be caused by adsorption of ions (that carry charge through the liquid crystal) on the surface of the nanoparticles.